Magnetic porphyrin-based metal organic gel for rapid RhB removal and enhanced antibacterial activity by heterogeneous Photo-Fenton reaction under visible light. (September 2022) - Gu, Dongxu; Liu, Yu; Zhu, Hongyu; Gan, Ying; Zhang, Biao; Yang, Weiting; Hao, Jianyuan
Abstract: Nanomaterials with visible light-driven catalytic ability are beneficial in controlling environmental pollutants. Porphyrin-based metal organic gel (MOG) was herein synthesized in one step and magnetic metal organic gel (MMOG) was successfully prepared via in-situ reaction of MOG and Fe3 O4 . This MMOG was developed as a novel visible light assisted Fenton-like catalyst. The catalytic experiments showed the high photo-Fenton activity of MMOG in the degradation of Rhodamine B (RhB) in the presence of visible light and H2 O2 with a RhB degradation efficiency of 94.2% within 40 min. Notably, the obtained MMOG can kill E. coli and S. aureus with high killing rate (>99.999%) under visible light. Importantly, the MMOG can be recovered simply by an external magnetic field due to the unique magnetic property. This easily synthesized MMOG with photo-Fenton activity under visible light and magnetic property makes MOG based on the photo-Fenton reaction a prospective material for the environmental and biomedical applications. Graphical abstract: A porphyrin-based magnetic metal organic gel (MMOG) as an efficient photo-Fenton degradation of organic pollutants and antibacterial material, which can be utilized as a multifunctional environmental remediation material. Image 1 Highlights: A porphyrin-based metal organic gel (MMOG) photocatalyst with magnetic center was prepared. MMOG and H2 O2 formed a photocatalysis-Fenton synergy system. The synergistic system demonstrated efficient photodegradation activity and antibacterial activity.